2023
DOI: 10.3390/jcm12051835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Anxiety on Postoperative Outcomes and Sleep Quality in Patients Undergoing Laparoscopic Gynecological Surgery

Abstract: Objective: Preoperative anxiety is a psychological state that commonly occurs before surgery and may have a negative impact on postoperative outcomes. This study aimed to investigate the effects of preoperative anxiety on postoperative sleep quality and recovery outcomes among patients undergoing laparoscopic gynecological surgery. Methods: The study was conducted as a prospective cohort study. A total of 330 patients were enrolled and underwent laparoscopic gynecological surgery. After assessing the patient’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…On the contrary, there are also studies indicating that there is no relationship between educational status and preoperative anxiety. [22,23] In the current study, there was no statistically significant difference between educational status and anxiety. In most of the studies evaluating the relationship between health literacy and educational status, it is stated that as the level of education of individuals increases, the level of health literacy also increases.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…On the contrary, there are also studies indicating that there is no relationship between educational status and preoperative anxiety. [22,23] In the current study, there was no statistically significant difference between educational status and anxiety. In most of the studies evaluating the relationship between health literacy and educational status, it is stated that as the level of education of individuals increases, the level of health literacy also increases.…”
Section: Discussioncontrasting
confidence: 48%
“…In some studies, it was found that people with higher level of education had higher levels of preoperative anxiety. [2,12,14,15,21,22] This result was explained by the fact that as the level of education of patients increased, their awareness of the risks of anesthesia and surgery increased, and that these individuals were more capable of expressing their anxiety. [21] However, individuals with a high level of education are expected to research more and be able to cope with stress more comfortably since they have higher knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that preoperative anxiety and depression adversely affect sleep quality both before and after surgery. Higher levels of psychological distress correlate with poorer sleep quality during the perioperative period, leading to a higher incidence of PSD (Du et al, 2023; Gu et al, 2023; Huang et al, 2021; Mansano-Schlosser et al, 2017; S. J.Wang et al, 2022; Z.Wang et al, 2023; Wright et al, 2010).…”
Section: Resultsmentioning
confidence: 99%